Impact of entrepreneurial support institutions on the entrepreneurship and the business environment in Zagreb – a case study of ZICER (Vallis Aurea, 2022)
Entrepreneurial support institutions off er a wide range of services to their tenants, which in the long run aff ects their development, the development of the local environment in which they operate and the development of the overall Croatian economy. The aim of this paper is to examine the impact of entrepreneurial support institutions on the entrepreneurship and the business environment in Zagreb, thecapital of Croatia. Throughout the paper, the method of description, comparison, deduction and synthetic were used. The problem investigated in the paper refers to the question of the success of ESI in meeting theneeds of creating an entrepreneurial environment in the area in which they operate. Through the example of the Zagreb Innovation Center (ZICER), empirical data were collected by a survey questionnaire to examine the satisfaction and the acceptance of the services by their users. Conducting primary research sources, the authors proved that users are satisfi ed with the received services, showed the importance and benefi t that users, local and national economy have from entrepreneurial support institutions. The results of the research can be the basis for further research and strengthening the role of entrepreneurial support institutions.